1994
DOI: 10.3109/09687689409160436
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of the cytoplasmic domain of phospholamban by NMR and CD

Abstract: Nuclear magnetic resonance (NMR) and circular dichroism (CD) spectroscopy have been used to characterize the conformation of the putative cytoplasmic domain of phospholamban (PLB), an oligomeric membrane-bound protein which regulates the activity of the cardiac sarcoplasmic reticulum Ca(2+)-dependent ATPase. In aqueous solution the 25-residue peptide adopts a number of rapidly interconverting conformers with no secondary structural type obviously predominating. However, in trifluoroethanol (TFE) the conformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…The principle elements of the chemical shift tensors are represented according to the convention σ 33 ≥ σ 22 ≥ σ 11 . Figure 3 shows the solid-state 2 H NMR powder pattern spectra of site-specific CD 3 -labeled WT-PLB (at residues Leu51, Ala24, and Ala15) and P-PLB (at residue Ala15) incorporated into POPC MLVs.…”
Section: Analysis Of 2 H and 15 N Solid-state Nmr Spectroscopic Datamentioning
confidence: 99%
“…The principle elements of the chemical shift tensors are represented according to the convention σ 33 ≥ σ 22 ≥ σ 11 . Figure 3 shows the solid-state 2 H NMR powder pattern spectra of site-specific CD 3 -labeled WT-PLB (at residues Leu51, Ala24, and Ala15) and P-PLB (at residue Ala15) incorporated into POPC MLVs.…”
Section: Analysis Of 2 H and 15 N Solid-state Nmr Spectroscopic Datamentioning
confidence: 99%
“…19,37 Isolated cytoplasmic domains of PLB have been observed to be unstructured in aqueous solution, but structured in SDS micelles and TFE. 31,32 Our CD spectra showed that the isolated cytoplasmic domain (PLB 1-25 K) is also unstructured in the presence of lipid bilayers ( Figure 5B). This is, to our knowledge, the first evidence that the isolated cytoplasmic domain of PLB remains unstructured in the presence of lipid bilayers.…”
Section: Structure and Inhibitory Function Of Plb Domainsmentioning
confidence: 99%
“…26,30 However, the isolated cytoplasmic domain of PLB is primarily unstructured in aqueous solution, 31 and only forms an ␣-helical conformation when prepared in SDS or trifluoroethanol (TFE) solutions. 31,32 The lack of functional effect observed in the isolated cytoplasmic domain of PLB could be due to a lack of structure in the peptide, the low affinity of the free cytoplasmic peptide for the Ca-ATPase, or incorrect positioning of the peptide. In order for the cytoplasmic domain of PLB to have a functional effect on the Ca-ATPase, it is likely than the peptide must be anchored to the membrane surface in a configuration that optimizes the potential for interaction with the Ca-ATPase.…”
Section: Introductionmentioning
confidence: 99%
“…2A). This finding was not surprising, given that in both PLB and WSPLB residues 1–25 are essentially unstructured in the absence of detergents or lipids (30–34). A recent NMR structure of the monomeric mutant C41F of PLB in DPC micelles by Zamoon et al (35) revealed that residues 2–13 are in fact α ‐helical in the presence of dodecylphospholcholine (DPC) detergents.…”
Section: Thermal Denaturationmentioning
confidence: 90%